Penerapan Ui/Ux Dengan User Centered Design Pada Aplikasi Android Penjualan Pada Toko Nataz Collection - Muhammad Ikhwan Fakhmi; Nurul Huda; Firamon Syakti (JSAI (Journal Scientific and Applied Informatics), 2023)
The development of technology today has grown rapidly, especially in the development of applications. Application development cannot be separated from the role of User Interface (UI) and User Experience (UX) because in the development of applications must be neat and organized. Some sales applications that are available today can display catalogs of several products that are sold. One of them is the Nataz Collection Store which has begun to shift to digital-based purchases. The purpose of this study is also to find out how well the UI / UX implementation is used, the method used to create UI / UX design in this study is the User Centered Design method. User Centered Design focuses on design and evaluation built from the initial steps to continuous implementation. This research resulted in a mobile application UI/UX design that conforms to sound design principles and uses current sales trends in Nataz Collection Stores. If the user interface is designed well, users will interact with the app more positively, increasing user retention and sales. The results of the study were measured using the System Usability Scale (SUS) where the assessment results given to 15 respondents resulted in a score of 83.00. This shows that the design of the Android-based Nataz Collection Store sales application can be accepted by users and get good value in usability.